Genome sizes and repeatome evolution in zoantharians (Cnidaria: Hexacorallia: Zoantharia) - Fourreau, Chloé Julie Loïs; Kise, Hiroki; Santander, Mylena Daiana; Pirro, Stacy; Maronna, Maximiliano M. [UNESP]; Poliseno, Angelo; Santos, Maria E.A.; Reimer, James Davis (PeerJ, 2023)
Across eukaryotes, large variations of genome sizes have been observed even between closely related species. Transposable elements as part of the repeated DNA have been proposed and confirmed as one of the most important contributors to genome size variation. However, the evolutionary implications of genome size variation and transposable element dynamics are not well understood. Together with phenotypic traits, they are commonly referred to as the ‘‘C-value enigma’’. The order Zoantharia are benthic cnidarians found from intertidal zones to the deep sea, and some species are particularly abundant in coral reefs. Despite their high ecological relevance, zoantharians have yet to be largely studied from the genomic point of view. This study aims at investigating the role of the repeatome (total content of repeated elements) in genome size variations across the order Zoantharia. To this end, whole-genomes of 32 zoantharian species representing five families were sequenced. Genome sizes were estimated and the abundances of different repeat classes were assessed. In addition, the repeat overlap between species was assessed by a sequence clustering method. The genome sizes in the dataset varied up to 2.4 fold magnitude. Significant correlations between genome size, repeated DNA content and transposable elements, respectively (Pearson’s correlation test R2 = 0.47, p = 0.0016; R2 = 0.22, p = 0.05) were found, suggesting their involvement in the dynamics of genome expansion and reduction. In all species, long interspersed nuclear elements and DNA transposons were the most abundant identified elements. These transposable elements also appeared to have had a recent expansion event. This was in contrast to the comparative clustering analysis which revealed species-specific patterns of satellite elements’ amplification. In summary, the genome sizes of zoantharians likely result from the complex dynamics of repeated elements. Finally, the majority of repeated elements (up to 70%) could not be annotated to a known repeat class, highlighting the need to further investigate non-model cnidarian genomes. More research is needed to understand how repeated DNA dynamics relate to zoantharian evolution and their biology.
Keywords: C-value enigma; Genome size; Repeated DNA; Transposable elements; Zoantharia